Research on the Dynamics of Geological Drilling Rig against Drill Pipe Impact - Shixin Bai; Zhijian Liu; Jin Wang (Shock and Vibration)
With the ever-increasing demand for resources, the task of geological surveys has increased rapidly, and automated geological drilling rigs that can improve the efficiency of geological surveys have become the mainstream research direction. Automated geological drilling rigs can improve construction efficiency, reduce labor intensity, and effectively reduce construction accidents. During the construction of geological survey operations, accidents such as drill breakage, stuck drill, and equipment damage, which are easily caused by drill pipe impact, occur from time to time. Therefore, drill pipe impact dynamics is currently a hot topic in academic research, but there are few studies that combine automated geological drilling rigs with drill pipe impact. This article starts with the research on the hydraulic system of the power head of the automatic drilling rig and studies the dynamics of the damage of the power head of the drilling rig caused by the impact of the drill pipe by means of hydraulic valve torque limit and closed-loop control of the speed. The oil valve group reduces the reverse torsional impact of the drill pipe on the hydraulic motor. At the same time, the requirements for the selection and pressure setting of the relief valve in the buffer filling oil valve group are proposed. The natural frequency of the relief valve is not less than 20 Hz, and the pressure is set to the working pressure 1.25 times. The effects of shock with or without the buffer filling oil valve group and the oil supply line on the power head motor were compared. The research results of this paper can provide theoretical reference and design basis for subsequent development of automated drilling rigs.